A real-world experience of transition to robotic-assisted thoracic surgery (RATS) for lung resections - Palleschi, Alessandro; Mattioni, Giovanni; Mendogni, Paolo; Tosi, Davide (Frontiers in Surgery, 2023)
Objective. We report our experience of transition from uniportal Video-Assisted Thoracic Surgery (VATS) to Robot-Assisted Thoracic Surgery (RATS) with da Vinci Xi for lung resections, exposing short-term results. Materials and Methods. This is a single center, retrospective analysis of RATS lung resections performed between April 2021 and September 2022. The approach changed over time, starting from an initial 4-arm approach with 4 incisions. Alternative RATS approaches were used, such as uniportal and biportal. Results. Sixty-three RATS mediastinal and lung procedures were performed during a 17-month period. Sixteen were lobectomies, 7 segmentectomies, and 6 wedge resections. The most common indication for anatomical lung resection was NSCLC. A uniportal approach was used for 2 simple segmentectomies and a biportal RATS was performed in 5 lobectomies and 2 segmentectomies. A mean number of 8.1 lymph nodes and a mean of 2.6 N2 and 1.9 N1 stations were resected during surgery. No nodal upstaging was observed. Negative resection margins were 100%. There were 2 (7%) conversions, one to open surgery and one to VATS. Eight (28%) patients experienced complications. Thirty-day mortality was 0. Discussion. High ergonomic and high-quality view were immediately observed. During uniportal RATS, arm collisions were encountered. The presence of a VATS-skilled surgeon at the operating table is believed to be necessary. Conclusions. RATS was safe and effective, and from the surgeon’s standpoint, several practical advantages over VATS were observed. Further analysis of outcomes will help better understand the value of this technology.